The Impact Of Financial Safety On The Market Value Of The Shares Of Insurance Companies Listed On The Damascus Stock Exchange (Latakia University Journal - Economic and Legal Sciences Series, 2022)
The research aimed to identify the impact of financial safety with its indicators (liquidity, profitability) on the market value of the shares of insurance companies listed on the Damascus Stock Exchange, and the time period was chosen from 2009-2019.The research relied on the analytical descriptive approach, and the method of analysis for the financial statements was used for six insurance companies listed on the Damascus Securities Exchange that were disclosed. It also relied on analyzing and testing hypotheses on some statistical tests available in the EVIEWS program, such as the multiple regression model according to three forms: , fixed effects, random effects, and the use of time-series inactivity tests and tests for the quality of models representation.It reached the most important results:- There is a significant effect of the liquidity ratio and profitability ratios on (the market share price).- Increasing the liquidity ratio by 1% leads to an increase in the market share price by 269.75 SP, and this increase is significant.- An increase in the profitability ratio by 1% leads to an increase in the market share price by 191.65 SP, and this increase is significant.